Distribución de síntomas en pacientes con TEP según su relación VD/VI en angiografías por tomografías computadas - Sanhueza Z., Andrés; Díaz P., Juan Carlos; Weisz C., Jose; Prieto R., Juan Carlos; Araya R., Rodrigo; Cabezas R., Mariela; Olivares S., Pablo (Revista Hospital Clínico Universidad de Chile, 2014)
Background: Pulmonary embolism (PE) is a frequent and mortal condition if not managed properly. Symptoms are various and some are associated with severity in PE. Computed tomography angiography (AngioCT) is the most used imaging technique to diagnose and estimate the severity in PE. Objective: Describe the distribution of symptoms in patient with RV/LV (right ventricle/left ventricle)>1 or <1, in order to associate them with severity. Methods and Materials: We reviewed medical records and imaging of patients with AngioCT diagnostic of PE, from 2011 to 2013. PE was considered as contrast fill defect in two pulmonary artery slides. The RV/LV relation was measured in the 4 chamber level. Results: Fifty six patient were studied, 23% had RV/LV>1 of which 62% were female. Symptoms in RV/LV>1 patients: lower extremities pain or swelling: 46%, dyspnea: 31%, cough: 23%, palpitation: 8%, presyncope: 8%, 31% of patient had multiple symptoms. Symptoms in RV/LV<1 patients: lower extremities pain or swelling: 58%, dyspnea: 40%%, cough: 26%, palpitation: 14%, hemoptysis: 7%, presyncope: 5%, 51% of patient had multiple symptoms. Conclusions: The distribution of PE symptoms relatively concurs with literature. The most frequent clinical finding was lower extremities pain or swelling followed by dyspnea. Females and older patients had more RV alterations. Presyncope was more frequent in RV/LV>1 patients. Other symptoms than lower extremities pain or swelling or dyspnea were more frequent in RV/LV>1 . In RV/LV<1 patient was more common to find multiple symptoms at diagnostic.